2015
DOI: 10.1186/s12889-015-1911-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a systematic approach to promote intersectoral collaboration in comprehensive school health promotion-a multiple-case study using quantitative and qualitative data

Abstract: BackgroundWe report on the longitudinal quantitative and qualitative data resulting from a two-year trajectory (2008–2011) based on the DIagnosis of Sustainable Collaboration (DISC) model. This trajectory aimed to support regional coordinators of comprehensive school health promotion (CSHP) in systematically developing change management and project management to establish intersectoral collaboration.MethodsMultilevel analyses of quantitative data on the determinants of collaborations according to the DISC mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 26 publications
0
29
0
6
Order By: Relevance
“…Assessment of the applied models revealed that there was a fairly good variation in studies. The applied models were: DISC (17)(18)(19)(20), Bergen (11,14), Himelman (15), network analysis (16), social network analysis (10,21), act for life collaboration continuum (22), Tukman (23), collective impact approach (24), system analysis (25), and logic (26,27).…”
Section: Results Of the Extraction Of Criteria Models And Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of the applied models revealed that there was a fairly good variation in studies. The applied models were: DISC (17)(18)(19)(20), Bergen (11,14), Himelman (15), network analysis (16), social network analysis (10,21), act for life collaboration continuum (22), Tukman (23), collective impact approach (24), system analysis (25), and logic (26,27).…”
Section: Results Of the Extraction Of Criteria Models And Indicatorsmentioning
confidence: 99%
“…A positive experience of collaboration/the desire to continue the collaboration, and sustainability in the collaboration: Sustainability in collaboration is de ned as the gradual development of a sustainable collaboration (20). If collaborators have a positive experience of their previous collaborative process, they will need less energy to make internal changes and will feel more support for policies affecting them, which will eventually help them create a sustainable collaborative process (18).…”
Section: Discussionmentioning
confidence: 99%
“…Analysts also study the impact of network structures [63,[74][75][76], arguing that networks rely on network efficiency and density [63,75,76]. In contrast, network breadth can decrease performance, creating difficulties in reaching consensus and creating trust within a [63,[74][75][76] • Network geography [50,67,77] • Creating connectivity/consensus [78] • Co-creation [79] • Planning [80] • Managing performance [81,82] • Continuous learning [83,84] • Sharing information [85] • Pooling resources/expertise [13,86,87] • Committed/credible leaders [88][89][90][91][92][93] • Nurturing linkages [41,51,[94][95][96][97] • Aligning goals and creating shared understandings [95,98] Organisation level (15 studies)…”
Section: Leadership Mediamentioning
confidence: 99%
“…Interorganizational collaboration makes possible information exchange, advice giving and pooling of resources for successful implementation (Palinkas et al, 2014). Moreover, collaboration requires supportive perceptions, intentions, and actions (Pucher, Candel, Krumeich, Boot, & De Vries, 2015). Tooher et al, (2017) elucidated that the focus of the study in collaboration is on process networks and sectoral agenda alignment.…”
Section: Inter-organizational Collaborationmentioning
confidence: 99%